2008
DOI: 10.1097/acm.0b013e31815c63b6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Dual Degree: Development of a Five-Year Program in Leadership for Medical Undergraduates

Abstract: The current state of physician leadership education consists mainly of executive degree programs designed for midcareer physicians. In 2004, the authors proposed that, by educating medical students in physician leadership and integrating this with a business management or public health degree program, graduates, health care organizations, and communities would benefit sooner. Given the lack of program models to guide program integration and development, the authors began a one-year inquiry to build a model lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 7 publications
2
47
0
1
Order By: Relevance
“…The selection process constituted submission of written materials followed by, for a selected subset of candidates, the MPI process. We derived the attributes of successful LEAD candidates from the literature on leadership 11,12 and through LEAD faculty consensus. These desired attributes were communicated to the pool of potential applicants and blueprinted onto (aligned with) questions asked during the MPI process.…”
Section: Methodsmentioning
confidence: 99%
“…The selection process constituted submission of written materials followed by, for a selected subset of candidates, the MPI process. We derived the attributes of successful LEAD candidates from the literature on leadership 11,12 and through LEAD faculty consensus. These desired attributes were communicated to the pool of potential applicants and blueprinted onto (aligned with) questions asked during the MPI process.…”
Section: Methodsmentioning
confidence: 99%
“…One program involves an integrated leadership and medical degree curricula, but this program requires an additional year of training, something most medical schools and medical students are not likely to choose. 22 Another medical school, the University of Wisconsin School of Medicine, has a program called LOCUS (Leadership Opportunities with Communities, the Underserved, and Special Populations) that seeks to improve medical students' leadership, knowledge, and skills through community service, but the program is not a curricular offering but, instead, a longitudinal, extracurricular activity. 23 Finally, the American Medical Student Association conducts an annual Primary Care Leadership Training Program that focuses on primary care, leadership skills, curricular reforms, and health policy issues, 24 but only a limited number of medical and dental students may attend.…”
Section: Althoughtheushealthcaresystemmentioning
confidence: 99%
“…One study [7] found that medical directors with management degrees were more likely to provide transformational leadership than those without training; however, many indispensable attributes of a good executive such as the ability to listen, communicate and collaborate are intrinsic and hard to teach [8 ].…”
Section: What Business Education Option Is Best?mentioning
confidence: 99%